Description and hierarchy of ductile deformation events in the Camalaú region, state of Paraíba, central portion of the Alto Moxotó Terrane, Borborema Province, Brazil - Lauro Montefalco Santos; Caio Santos Pereira; Haroldo Monteiro Lima; Pedro Guedes; Roberta Medeiros; Jefferson Silva; José Neto; Glenda Santos; Mariana Paixão (Journal of the Geological Survey of Brazil, 2020)
The Borborema Province (NE Brazil) has a long history of deformation, magmatism, and metamorphism during the Precambrian Eon. Thus, it represents a natural laboratory to investigate widely developed ductile-deformation markers, such as major fold belts and large-scale shear zones. This paper describes the structural evolution of a complex folded area of the Alto Moxotó Terrane, Central Borborema Province. In this region, para-derived rocks of the Sertânia Complex are intruded by orthogneisses and migmatitic orthogneisses. The Geophysical magnetometric expressions of the Borberma Province are characterized by strong aligned and folded magnetic lineaments and integrated structural analysis allowed us to identify three ductile deformation episodes. Brittle tectonics is also present, but not described. D1 stage represents the basement structural framework restricted to local structural windows of ancient orthogneisses and migmatites that are not mappable at the working scale. D2 deformation is widespread throughout the Central Borborema Province, producing nappes that mark top-to-NW tectonic vergence. Foliation and lineation attitudes are compatible with progressive deformation from tangential to strike-slip tectonics (i.e. D2 to D3). The latter is associated with the NE-SW Xinxó and Congo-Cruzeiro do Nordeste sinistral strike-slip shear zones, producing refold patterns that resemble Type-3 interference geometry. Based on airborne magnetic geophysical imaging interpretations and mesoscopic observations, we suggest that progressive deformation strongly affected the region and overprinted at large-scale early formed rocks.